Synthesis and characterization of zinc oxide nanoparticles-carbon composite derived from pineapple peel wastes for adsorption of methylene blue from solution and photocatalytic activity - Salsa Putri Alzura; Vienna Saraswaty; Safri Ishmayana; Yudha Prawira Budiman; Diana Rakhmawaty Eddy; Evyka Setya Aji; Diah Ratnaningrum; Een Sri Endah; Hanny Meirinawati; Henry Setiyanto (Case Studies in Chemical and Environmental Engineering)
Synthetic dye effluent poses substantial environmental issues due to its toxicity. In this work, a biosorbent derived from pineapple peels and modified with zinc oxide nanoparticles namely ZnONPs/PPWB, was prepared for the removal of cationic dyes, specifically methylene blue (MB), from aqueous solution. The ZnONPs/PPWB composite biosorbent was prepared through a facile green synthesis of zinc oxide nanoparticles utilizing pineapple peel wastes as the source of reducing agent and carbon sources, followed by a calcination at a low temperature of 400 °C for 2 h. The properties of the prepared composite biosorbent were characterized using Brunauer-Emmet-Teller (BET) surface area, scanning electron microscopy (SEM), X-ray diffraction (XRD) and fourier transform infra-red (FTIR) analyses. Several key factors, including pH, initial MB concentration, contact time, and biosorbent dosage as well as photocatalytic activity were investigated. The adsorption of MB on ZnONPs/PPWB is well described by the Freundlich model (R2 = 0.9842) and follows the Elovich kinetic model (X2 = 0.7390). The calculated maximum adsorption capacity of the ZnONPs/PPWB composite biosorbent (qmax = 65.43 mg/g) was 1.85 folds higher compared to the non-composite biosorbent (PPWB) (qmax = 35.21 mg/g) under the following conditions; adsorbent dose of 10 mg/30 mL, pH 7, and initial MB concentration of 20 mg/L. In addition, under solar irradiation, the composite ZnONPs/PPWB biosorbent exhibited the greater MB removal efficiency than non-irradiated ZnONPs/PPWB. In summary, this work highlights the effectiveness and feasibility of transforming agricultural wastes into ZnONPs/PPWB composite biosorbent for the removal of cationic dyes from wastewater.